Barriers to Referral for Palliative Radiotherapy by Physicians: A Systematic Review. Issue 1 (January 2019) - Livergant, J.; Howard, M.; Klein, J.
Abstract: Aims: Palliative radiotherapy (PRT) can relieve symptoms and improve quality of life, but remains underutilised, possibly due to lack of referrals. We conducted a systematic review to study barriers impeding referral for PRT. Materials and methods: We searched EMBASE and MEDLINE to identify published studies of physician barriers to PRT referral. Data were synthesised using the percentage of respondents to the surveys in these studies who identified a given factor as a significant barrier to PRT referral. Barriers were categorised using a conceptual framework for radiotherapy access described by Sundaresan et al . (Aust Health Rev 40 (1), 2016, 11–18.) Results: EMBASE and MEDLINE searches returned 364 distinct papers. Of these, 11 papers (reporting on 12 cohorts of survey respondents) met the study inclusion criteria. All used a cross-sectional survey design. Seven cohorts included mainly family physicians, one surveyed mostly radiation oncologists, one surveyed hospice professionals and one surveyed members of the American Society of Clinical Oncology, the American Society of Radiation Oncology and the American Academy of Hospice Palliative Medicine. Many factors were identified as strongly influencing referral decisions. Only two cohorts of respondents were asked whether patient wishes influence referrals, but most (78–82%) respondents in these cohorts agreed that it was an important influence. Other important barriers included functional status (five cohorts asked, cited as a strong influence by 53–78% of respondents), short life expectancy (three, 44–59%), treatment length (five, 51–58%), inconvenience (six, 24–65%), cancer type (three, 55–80%), uncertainty of benefits (seven, 18–54%) and toxicity concerns (11, 18–43%). Hospice professionals most frequently cited factors related to expense of treatment. Conclusions: Published high-quality data on barriers to PRT referral are limited to survey studies. Barriers to PRT referral include referrers' unfamiliarity regarding risks and benefits, cumbersome referral processes and perceived inconvenience of treatment. Interventions to increase referrals should be tailored to different professional groups and may include increased expert participation in multidisciplinary palliative care, shortening treatment courses and in-person interprofessional education. Highlights: Few studies exist on barriers to referral for palliative radiotherapy. Perceived inconvenience and knowledge of radiotherapy risks/benefits limit referrals. Patient wishes strongly influence referrals but are rarely asked about in surveys. Multidisciplinary care and in-person education efforts can increase referrals.